Dynamic identification of candidate genes associated with higher tocopherol biosynthesis in Brassica napus seeds - Zhang, Yunyun; Qin, Ping; Liu, Yajun; Liu, Yingnan; Li, Wenjing; Luo, Chunjuan; Chen, Peng; Zhang, Chunyu (Frontiers in Plant Science, 2025)
Vitamin E is a crucial fat-soluble antioxidant playing vital roles in human health as well as the growth and development of plants and animals. Brassica napus L. (rapeseed) is recognized as the world’s second most important oilseed crop, serving as a primary source of vegetable oil and vitamin E. However, the regulatory network governing vitamin E biosynthesis during rapeseed seed development remains poorly understood. In this study, transcriptome analyses were conducted using two pairs of rapeseed germplasms with high-VE (YH) or low-VE (YL) contents across entire seed developmental stages (15–50 DAF, days after flowering). The relationship between chlorophyll catabolism and vitamin E accumulation was systematically investigated, and candidate genes associated with seed VE biosynthesis were identified. Key findings include greater vitamin E accumulation observed in the high-VE line, primarily attributed to sustained VE biosynthesis during late seed development (45–50 DAF). Through transcriptome and weighted gene co-expression network analysis (WGCNA) during late seed development (35–50 DAF), four key regulatory modules were revealed, highlighting seven hub genes involved in chlorophyll catabolism and vitamin E biosynthesis. Additionally, two candidate loci on chromosomes A03 and C08 were identified via bulked segregant analysis sequencing (BSA-seq), along with five candidate genes (e.g., BnA03g0107720) proposed as critical regulators for B. napus seed vitamin E biosynthesis. These results contribute to an advanced understanding of the regulatory mechanisms underlying seed VE biosynthesis in oilseed crops and provide valuable genetic resources for enhancing rapeseed nutritional quality through vitamin E biofortification.